Integrasi Nilai –Nilai Keislaman Dalam Pembelajaran PAI Berbasis TIK di SMAN 4 Kota Ternate - Salim, Sartika; Ismail, Radjiman; Abbas, Sukardi; Agus, Agus; Ahmad, Samlan Hi (Peneliti.net, 2025)
This study aims to describe the integration of Islamic values in Islamic Religious Education (PAI) learning based on information and communication technology (ICT) at SMA Negeri 4 Kota Ternate. A descriptive qualitative approach was employed, using observation, interviews, and documentation as data collection techniques. The findings indicate that lesson planning is systematically carried out through school policies requiring the use of Islamic digital media in lesson plans. The learning process applies a blended learning model by utilizing PowerPoint, Islamic videos, and interactive applications that enhance student engagement, although challenges remain such as limited internet access, unequal device ownership, and digital distractions. The impact of ICT-based learning includes improved understanding, religious attitudes, and positive student habits. However, the evaluation system is still weak and requires more structured affective assessment instruments. This study highlights the importance of synergy between school policies, teacher competence, and evaluation support to optimize the integration of Islamic values through ICT-based learning.